2019
DOI: 10.1016/j.sjbs.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of off-road vehicles on soil and vegetation in a desert rangeland in Saudi Arabia

Abstract: Off-road vehicle driving is considered as main contributor to land degradation in arid regions. This study examined the impact of off-road vehicles (ORV) on soil and vegetation in a natural recreational desert meadow of Raudhat Khuraim, Saudi Arabia. Vegetation canopy cover and plant height away from road tracks were assessed. Also, species density and canopy cover, bare ground cover and soil attributes were assessed in four microhabitats; tracks, inter-tracks, verges, and away from vehicle tracks (undisturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Turfy swamps are usually located in valleys with perennially accumulated water, and in order to ensure the safe operation of highways, drainage ditches parallel to the highway are built, resulting in a large amount of water loss. Many scholars have reported that wetland drainage can change the physical properties such as density and water content of the original soil [23,24] and cause soil nutrient loss [25]. In any case, there is still a lack of knowledge about how soil microorganisms respond to road drainage and heavy metal pollution in turfy swamps.…”
Section: Introductionmentioning
confidence: 99%
“…Turfy swamps are usually located in valleys with perennially accumulated water, and in order to ensure the safe operation of highways, drainage ditches parallel to the highway are built, resulting in a large amount of water loss. Many scholars have reported that wetland drainage can change the physical properties such as density and water content of the original soil [23,24] and cause soil nutrient loss [25]. In any case, there is still a lack of knowledge about how soil microorganisms respond to road drainage and heavy metal pollution in turfy swamps.…”
Section: Introductionmentioning
confidence: 99%
“…In the two areas studied here, the soil was subjected to frequent vehicle passage and that may lead to damage seeds and the new seedlings. Off-road vehicle driving in the Saudi Arabia rangelands contributed to soil compaction and the soil bulk density was 38% higher under the motor vehicle tracks than that of undisturbed soils (Assaeed et al 2018). Compacted soil exposes seeds to predators, inhibits seed germination, and impedes seedling growth (Kozlowski 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ORV traffic can alter habitat structure and function through alterations to physiochemical properties of soil, loss of vegetative cover, and changes in plant community structure and function (Slaughter et al, 1990;Navas Romero et al, 2019;Sumanapala and Wolf, 2019), which often results in undesirable consequences for the fauna that inhabit them (Schlacher and Thompson, 2008;Cole, 2019). For instance, soils can be physically damaged through increased compaction, which may alter the success of certain plant species, altering species diversity (Brown and Schoknecht, 2001;Assaeed et al, 2019). While vegetation loss is common with ORV activity (Al-Awadhi, 2013;Cheung et al, 2021), community level responses have also been found, including alterations in species composition and conditions that may favor the introduction and spread of invasive plants (Milchunas et al, 2000;Assaeed et al, 2019;Navas Romero et al, 2019).…”
Section: Introductionmentioning
confidence: 99%